KESENJANGAN SOSIAL DI JAKARTA DALAM FOTOGRAFI JURNALISTIK: Social Disparities in Jakarta Through Photojournalism - Alfath Fajar; Silvia Amanda Aurelia; Erlina Novianti; Pongky Adhi Purnama (Universitas Trisakti, 2025)
Social Disparities in Jakarta Through Photojournalism. Jakarta is known for its numerous slum areas, a result of rural-to-urban migration, exemplified in places like Petamburan along the Ciliwung River. The stark social disparities between the affluent and the impoverished are evident in these areas. The aim of this research is to provide a perspective on these disparities through photojournalism, utilizing Practice-Based Research methodology to capture images that focus on social inequalities and technical aspects. The research produced five photographic works using photojournalistic techniques, showcasing the disparities between luxurious and impoverished lifestyles in Jakarta. In conclusion, the author utilized a photojournalistic approach to discuss the city's social disparities, highlighting the contradiction between luxurious living and poverty.